Effects of different menopausal hormone replacement regimens on body composition in Chinese women. (2nd November 2018) - Deng, Y.; Xue, W.; Wang, Y.; Zhu, S.; Ma, X.; Sun, A.
Abstract: Purpose: The aim of this study was to determine the effects of different menopausal hormone therapy regimens on body composition in healthy postmenopausal Chinese women. Materials and methods: One hundred and twenty-three healthy postmenopausal Chinese women were randomly assigned to either group A (0.625 mg conjugated equine estrogens [CEE] plus 100 mg micronized progesterone [MP]), group B (0.3 mg CEE plus 100 mg MP), or group C (0.625 mg CEE plus 10 mg dydrogesterone). Body composition was assessed by dual-energy X-ray absorptiometry. Results: One hundred and two women completed the trial at 1 year. A small but significant gain in lean body mass (619 ± 1019 g, p = 0.002) and a decrease of fat mass in all separate regions was observed in group A. A significant shift from gynoid to android fat distribution was observed in group B and group C (android/gynoid fat percentage ratios increased by 0.06 ± 0.08, p = 0.000 and 0.03 ± 0.08, p = 0.018, respectively), whereas no significant change was observed in group A (0.02 ± 0.06, p = 0.103). Conclusions: In healthy postmenopausal Chinese women, 0.625 mg of CEE combined with 100 mg of MP was associated with a more favorable fat distribution compared with 0.3 mg CEE plus 100 mg MP or 0.625 mg CEE plus 10 mg dydrogesterone.